2018
DOI: 10.1200/jco.2018.78.5246
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Measurements As Early Outcome Predictors in Diffuse Large B-Cell Lymphoma

Abstract: Pretreatment ctDNA levels and molecular responses are independently prognostic of outcomes in aggressive lymphomas. These risk factors could potentially guide future personalized risk-directed approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
398
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(431 citation statements)
references
References 32 publications
25
398
2
6
Order By: Relevance
“…Kurtz et al 26 13 In the current study, TP53 CHIP-carrying clone in one patient with DLBCL decreased in size at the time of developing ANKL. TP53 mutation was reportedly observed in only one of 14 ANKL patients in an exome-wide sequencing study.…”
Section: Discussionsupporting
confidence: 49%
“…Kurtz et al 26 13 In the current study, TP53 CHIP-carrying clone in one patient with DLBCL decreased in size at the time of developing ANKL. TP53 mutation was reportedly observed in only one of 14 ANKL patients in an exome-wide sequencing study.…”
Section: Discussionsupporting
confidence: 49%
“…From a precision medicine perspective, cfDNA genotyping may assist clinicians in choosing the most suitable option for targeted therapy through facilitated detection of individual genetic subclones responsible for relapse in DLBCL patients. There are other recent studies that evaluated plasma cfDNA levels in DLBCL (Kurtz et al, 2018), addressing whether it can predict or monitor therapy response or if it can predict tumor burden or prognosis of FL cases (Delfau-Larue et al, 2018). Using droplet digital PCR, Alcaide et al detected previously known mutations (e.g., EZH2 Y641 and STAT6 D419) in circulating tumor DNA in major B cell NHL subtypes (Alcaide et al, 2016).…”
Section: Noninvasive Clinical Applications Of Genomic Alterations Of mentioning
confidence: 99%
“…Circulating tumor DNA can be used in numerous ways to improve the management and characterization of both indolent and aggressive NHL (Table ). The application with immediate clinical implications involves replacing surveillance imaging with surveillance monitoring of ctDNA for detection of early relapse in DLBCL . The lead‐time offered by ctDNA monitoring creates a “window of opportunity” in which earlier institution of salvage therapy can be considered (Figure ).…”
Section: Clinical Applications Of Circulating Tumor Dnamentioning
confidence: 99%
“…Pretreatment ctDNA may also capture critical biologic information. Multiple studies have shown that pretreatment ctDNA levels in DLBCL correlate with markers of tumor burden such as advanced stage, LDH, and the international prognostic index (IPI) score . It is not clear, however, if other biologic processes affect pretreatment ctDNA levels.…”
Section: Clinical Applications Of Circulating Tumor Dnamentioning
confidence: 99%
See 1 more Smart Citation